2015
DOI: 10.1103/physreva.91.023609
|View full text |Cite
|
Sign up to set email alerts
|

Superfluid density and Berezinskii-Kosterlitz-Thouless transition of a spin-orbit-coupled Fulde-Ferrell superfluid

Abstract: We theoretically investigate the superfluid density and Berezinskii-Kosterlitz-Thouless (BKT) transition of a two-dimensional Rashba spin-orbit coupled atomic Fermi gas with both in-plane and out-of-plane Zeeman fields. It was recently predicted that, by tuning the two Zeeman fields, the system may exhibit different exotic Fulde-Ferrell (FF) superfluid phases, including the gapped FF, gapless FF, gapless topological FF and gapped topological FF states. Due to the FF paring, we show that the superfluid density … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 88 publications
3
10
0
Order By: Relevance
“…Furthermore, we observe from figures 6(a)-(c) that the transitions between the gapped and gapless states at moderate Zeeman fields and chemical potentials coincide with the prominent minima of D s diff . This is consistent with the findings of [48] where it was shown that the longitudinal component exhibits a clear minimum when the system becomes gapless. However, in figures 6(b), (c) we see the system reaching a gapped region again at large enough μ without such a drastic change of D s diff than at smaller values of μ.…”
Section: Components Of the Superfluid Weightsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, we observe from figures 6(a)-(c) that the transitions between the gapped and gapless states at moderate Zeeman fields and chemical potentials coincide with the prominent minima of D s diff . This is consistent with the findings of [48] where it was shown that the longitudinal component exhibits a clear minimum when the system becomes gapless. However, in figures 6(b), (c) we see the system reaching a gapped region again at large enough μ without such a drastic change of D s diff than at smaller values of μ.…”
Section: Components Of the Superfluid Weightsupporting
confidence: 93%
“…Therefore, by deploying SOC, one is able to stabilize FF phases considerably against thermal phase fluctuations and increase T BKT . This is similar to continuum studies [12,48,49] where it was proposed that FF states could be observed with the aid of SOC. The difference of λ=0 and λ=0.75 is further demonstrated in figure 1(e), where T BKT andq y for both the cases are plotted as a function of h x at h z =0.…”
Section: Phase Diagrams and The Bkt Temperaturesupporting
confidence: 87%
See 1 more Smart Citation
“…Hence, we assume that fermions pair at opposite momenta, ignoring the possibility of non-uniform superfluid phases [47][48][49][50]. In Eq.…”
Section: B Calculating the Saddle-point Thermodynamic Potentialmentioning
confidence: 99%
“…Mean field theory has been pushed to investigate the finite temperature behavior of spin-orbit coupled imbalanced Fermi gases, as well [194,195]. It was inferred that together with in-plane and out of plane Zeeman field, spin orbit coupling gives rise to BKT transition in two dimensions, both for gapped as well as gapless FF phases [194,195].…”
Section: Imbalance and Spin-orbit Coupling In Fermi Systemsmentioning
confidence: 99%